A computational study of CH4 storage in porous framework materials with metalated linkers: connecting the atomistic character of CH4 binding sites to usable capacity. Issue 7 (7th April 2016) - Tsivion, Ehud; Mason, Jarad A.; Gonzalez, Miguel. I.; Long, Jeffrey R.; Head-Gordon, Martin
Abstract : Open-metal sites are shown to significantly increase the CH4 storage capacity of porous materials. It is shown that the capacity is not determined solely by their CH4 affinity, but also by their geometry as well as by guest molecules. Abstract : To store natural gas (NG) inexpensively at adequate densities for use as a fuel in the transportation sector, new porous materials are being developed. This work uses computational methods to explore strategies for improving the usable methane storage capacity of adsorbents, including metal–organic frameworks (MOFs), that feature open-metal sites incorporated into their structure by postsynthetic modification. The adsorption of CH4 on several open-metal sites is studied by calculating geometries and adsorption energies and analyzing the relevant interaction factors. Approximate site-specific adsorption isotherms are obtained, and the open-metal site contribution to the overall CH4 usable capacity is evaluated. It is found that sufficient ionic character is required, as exemplified by the strong CH4 affinities of 2, 2′-bipyridine-CaCl2 and Mg, Ca-catecholate. In addition, it is found that the capacity of a single metal site depends not only on its affinity but also on its geometry, where trigonal or "bent" low-coordinate exposed sites can accommodate three or four methane molecules, as exemplified by Ca-decorated nitrilotriacetic acid. The effect of residual solvent molecules at the open-metal site is also explored, with some positive conclusions. Not only can residual solvent stabilize the open-metal site, surprisingly, solvent molecules do not necessarily reduce CH4 affinity, but can contribute to increased usable capacity by modifying adsorption interactions.